2019
DOI: 10.16919/bozoktip.588740
|View full text |Cite
|
Sign up to set email alerts
|

MCF-7 ve PC-3 Hücre Hatlarında, Hücre Canlılığı ve DNA Hasarı Üzerine TRPV4 Antagonisti RN 1734'ün Etkileri

Abstract: Hücre içi kalsiyum (Ca 2 +) sinyali; hücre proliferasyonu ve farklılaşması, gen transkripsiyonu, apoptozis gibi birçok hücresel süreçte rol oynar. Yapılan çalışmalarda Ca 2 + sinyalinin kanser ile ilişkili olduğu gösterilmiştir. Transient receptor potential vanilloid 4 (TRPV4) kanalları hücre zarında bulunan Ca 2 + geçirgen non-selekif katyon kanalıdır. TRPV4 kanalları vücutta birçok dokuda yaygın olarak eksprese edilmektedir. Hücre içi Ca 2 + miktarının düzenlenmesinde etkisi olan TRPV4 kanallarının kanser hü… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Cakır and Erden conducted a study in which RN-1734 at concentrations of 50 and 100 μM in human prostate (PC-3) and human breast (MCF-7) cancer cell lines caused DNA damage in the cells and significantly reduced cell viability (%) 14 . Bahari et al also found that the administration RN-1734 at concentrations of 1, 10, and 100 μM in the colorectal cancer cell line statistically decreased cell viability (%) 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cakır and Erden conducted a study in which RN-1734 at concentrations of 50 and 100 μM in human prostate (PC-3) and human breast (MCF-7) cancer cell lines caused DNA damage in the cells and significantly reduced cell viability (%) 14 . Bahari et al also found that the administration RN-1734 at concentrations of 1, 10, and 100 μM in the colorectal cancer cell line statistically decreased cell viability (%) 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al found that inhibition of TRPV4 channels in human hepatocellular carcinoma cells suppresses cell proliferation, induces apoptosis, and reduces migration ability 13 . In addition, Çakır and Erden found that the administration of RN-1734, a TRPV4 antagonist, in human prostate (PC-3) and human breast (MCF-7) cancer cell lines caused DNA damage in cells and reduced cell viability 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Pollutants, including pesticides, are known to spread quickly in the environment and human organs, leading to long-term health issues shortly after their introduction (Gavrilescu et al, 2015). Because of their significant metabolic activities, the liver is the main target organ for pesticide damage (Çakır and Erden, 2019). Hence, it is a global priority to protect human health from pesticides, pesticide-contaminated drinking water, and harmful air pollutants (Damalas and Koutroubas, 2016).…”
Section: Introductionmentioning
confidence: 99%